Long-range looping of a locus control region drives tissue-specific chromatin packing within a multigene cluster - Tsai, Yu-Cheng (Nucleic Acids Res, 2016)
The relationships of higher order chromatin organization to mammalian gene expression remain incompletely defined. The human Growth Hormone (hGH) multigene cluster contains five gene paralogs. These genes are selectively activated in either the pituitary or the placenta by distinct components of a remote locus control region (LCR). Prior studies have revealed that appropriate activation of the placental genes is dependent not only on the actions of the LCR, but also on the multigene composition of the cluster itself. Here, we demonstrate that the hGH LCR ‘loops’ over a distance of 28 kb in primary placental nuclei to make specific contacts with the promoters of the two GH genes in the cluster. This long-range interaction sequesters the GH genes from the three hCS genes which co-assemble into a tightly packed ‘hCS chromatin hub’. Elimination of the long-range looping, via specific deletion of the placental LCR components, triggers a dramatic disruption of the hCS chromatin hub. These data reveal a higher-order structural pathway by which long-range looping from an LCR impacts on local chromatin architecture that is linked to tissue-specific gene regulation within a multigene cluster.